The Peaceful Co-existence of Input Frequency and Structural Intervention Effects on the Comprehension of Complex Sentences in German-Speaking Children - Adani, Flavia; Stegenwallner-Schütz, Maja; Niesel, Talea (Frontiers in Psychology, 2017)
The predictions of two contrasting approaches to the acquisition of transitive relative clauses were tested within the same German-speaking participants aged from 3 to 5 years. The input frequency approach predicts that object relative clauses with inanimate heads (e.g., the pullover that the man is scratching) are comprehended earlier and more accurately than those with an animate head (e.g., the man that the boy is scratching). In contrast, the structural intervention approach predicts that object relative clauses with two full NP arguments mismatching in number (e.g., the man that the boys are scratching) are comprehended earlier and more accurately than those with number-matching NPs (e.g., the man that the boy is scratching). These approaches were tested in two steps. First, we ran a corpus analysis to ensure that object relative clauses with number-mismatching NPs are not more frequent than object relative clauses with number-matching NPs in child directed speech. Next, the comprehension of these structures was tested experimentally in 3-, 4- and 5-year-olds respectively by means of a color naming task. By comparing the predictions of the two approaches within the same participants, we were able to uncover that the effects predicted by the input frequency and by the structural intervention approaches co-exist and that they both influence children’s performance on transitive relative clauses, but in a way that is modulated by age. In all age groups, the animacy mismatch appears to explain children’s performances, thus, showing that the comprehension of frequent object relative clauses is enhanced compared to the other conditions. Starting with four-year-olds but especially in five-year-olds, the number mismatch supported comprehension, a facilitation that is unlikely to be driven by input frequency. These results reveal a sensitivity to animacy mismatch already in three-year-olds and show that animacy is initially deployed more reliably than number to interpret relative clauses correctly. Once children fine-tune their sensitivity to verb agreement information around age four, they are also able to deploy number marking to overcome the intervention effects. This study highlights the importance of testing experimentally contrasting theoretical approaches in order to characterize the multifaceted, developmental nature of language acquisition.